The role of endowment investment in achieving development: The Harvard University Experience as a Model - garoui, Sabah; Khouloufi, Wahiba (Journal of Human Sciences, 2022)
This study aims to highlight the developmental role of endowment investments in achieving development, through leading global experiences in endowment investments, which is the experience of Harvard University in the United States. The study concluded that the role of endowment investments is important in achieving development in its various dimensions, and it also played an important role in pioneering the higher education sector at Harvard University in the United States, through the management and management of endowment investments within Harvard University well and giving a spirit of competition to endowment projects in addition to their distinction. Transparency in the management of these funds and the strategic planning of the latter for the development and promotion of education at Harvard University in the United States.